2019
DOI: 10.1111/1752-1688.12743
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Urban Growth and High Residential Irrigation on Streamflow and Groundwater Levels in a Peri‐Urban Semiarid Catchment

Abstract: The impact of urbanization on groundwater is not simple to understand, as it depends on a variety of factors such as climate, hydrogeology, water management practices, and infrastructure. In semiarid landscapes, the urbanization processes can involve high water consumptions and irrigation increases, which in turn may contribute to groundwater recharge. We assessed the hydrological impacts of urbanization and irrigation rates in an Andean peri‐urban catchment located in Chile, in a semiarid climate. For this pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 51 publications
(117 reference statements)
2
16
0
Order By: Relevance
“…The basin hosts Santiago, the Chilean capital, with more than seven million inhabitants in the metropolitan area (approximately 40% of the nation's population) (INE, 2018). During past decades, the city has grown towards the Andes foothills (Romero et al, 1999;Pávez et al, 2010;Sanzana et al, 2019), where more than 30 sub-catchments are drained by ravines and gullies forming alluvial fans, posing an increasing risk to population (Lara et al, 2018). These ravines are in the western slope of Andes mountains, known as "Pre-Cordillera," where the highest altitude (3,250 m ASL) is the San Ramón hill in the Quebrada de Ramón catchment (Sepúlveda and Padilla, 2008).…”
Section: Study Areamentioning
confidence: 99%
“…The basin hosts Santiago, the Chilean capital, with more than seven million inhabitants in the metropolitan area (approximately 40% of the nation's population) (INE, 2018). During past decades, the city has grown towards the Andes foothills (Romero et al, 1999;Pávez et al, 2010;Sanzana et al, 2019), where more than 30 sub-catchments are drained by ravines and gullies forming alluvial fans, posing an increasing risk to population (Lara et al, 2018). These ravines are in the western slope of Andes mountains, known as "Pre-Cordillera," where the highest altitude (3,250 m ASL) is the San Ramón hill in the Quebrada de Ramón catchment (Sepúlveda and Padilla, 2008).…”
Section: Study Areamentioning
confidence: 99%
“…However, in the middle reach, we found no relationship between HAR and canopy height, and greater HAR was associated with lower density and cover here. The typical complexity of groundwater–surface water interactions in urban systems (Garcia‐Fresca & Sharp, 2005; Hardison, O'Driscoll, DeLoatch, Howard, & Brinson, 2009; Sanzana et al, 2019; Tubau, Vázquez‐Suñé, Carrera, Valhondo, & Criollo, 2017) makes it difficult to draw conclusions about the causal effects of HAR in this more urbanized reach, flowing partly through the University Campus. It is surprising that HAR was a relatively weak predictor of vegetation structure overall (affecting canopy height in the upper canyon, cover and density in the middle reach and not affecting any of our vegetation metrics in the lower reach), although the patterns we observed were consistent with water supply as a dominant influence on larger trees in the upper section of the stream.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the middle reach, we found no relationship between HAR and canopy height, and greater HAR was associated with lower density and cover here. The typical complexity of groundwater-surface water interactions in urban systems (Garcia-Fresca & Sharp, 2005;Hardison, O'Driscoll, DeLoatch, Howard, & Brinson, 2009;Sanzana et al, 2019;Tubau, Vázquez-Suñé, Carrera, Valhondo, & Criollo, 2017) It is tempting to assume that urbanization is typically paired with the removal of vegetation and thus systematically leads to a decline in vegetation. Even though this narrative that riparian forests decline through urbanization has long dominated the literature, in recent decades, authors have found evidence for canopy expansion along many urban streams in (semi)arid regions (Grossinger, Striplen, Askevold, Brewster, & Beller, 2007;Solins, Thorne, & Cadenasso, 2018;Villarreal, Drake, Marsh, & Mccoy, 2012;White & Greer, 2006 In terms of community composition, there is a consensus that increases in nonnative species occur along gradients of urbanization around the globe across multiple taxa (McKinney, 2006).…”
Section: Local Topography and Hydroclimatementioning
confidence: 99%
“…On one hand, the BFI could be higher in some urbanized catchments owing to water treatment facility releases during the dry period (Oudin et al, 2018), reduction in vegetation cover, or leakage in high-pressure potable water systems (Göbel et al, 2004;Lancia, Zheng, Yi, Lerner, & Andrews, 2019). On the other hand, BFI could be lower in some urbanized catchments in which groundwater pumping is intensive and the river-groundwater connection is cut by sealing the riverbanks (Braud et al, 2013;Brun & Band, 2000;Sanzana et al, 2019;Zektser & Everett, 2004). These two possible changes are observed in our catchment set, but for the majority, BFI decreased.…”
Section: Are There Differences Between Urbanized and Rural Catchmenmentioning
confidence: 99%